Hematopoietic Stem Cell Transplantation for Primary Immunodeficiencies - Gennery, Andrew R.; Albert, Michael H.; Slatter, Mary A.; Lankester, Arjan (Frontiers in Pediatrics, 2019)
The field of primary immunodeficiencies has pioneered many of the advances in haematopoietic stem cell transplantation and cellular therapies over the last 50 years. The first patients to demonstrate sustained benefit and prolonged cure from the primary genetic defect following allogeneic haematopoietic stem cell transplantation were patients with primary immunodeficiencies. Although primary immunodeficiency patients began the modern era of haematopoietic stem cell transplantation, the history is nevertheless short-in answer to the question “what is the long term outcome of patients transplanted for primary immunodeficiencies?” we often have to say that we do not know. We believe that most patients who undergo haematopoietic stem cell transplantation for primary immunodeficiencies should live a normal lifespan with a fully corrected immune system. We are now beginning to understanding long term outcomes, the relationship to the underlying genetic defect, age, and pre-morbid condition of the patient at time of transplantation, stem cell source and donor, and effect of pre-transplant cytoreductive chemotherapy conditioning. The long term consequences of post-transplant complications such as graft vs. host disease, veno-occlusive disease, or immune dysregulation are also being recognized. Additionally, some genetic defects have a systemic distribution, and we are learning the natural history of these defects once the immunodeficiency has been removed.